The Epidemiology of Vertebral Osteomyelitis in the United States From 1998 to 2013. Issue 2 (March 2018) - Issa, Kimona; Diebo, Bassel G.; Faloon, Michael; Naziri, Qais; Pourtaheri, Sina; Paulino, Carl B.; Emami, Arash
Abstract : Study Design: This is a epidemiological database analysis. Objectives: The objectives of this article are to assess the following characteristics of vertebral osteomyelitis (VO): (1) incidence and patient demographics, (2) mortality rate, (3) length-of-stay (LOS), and (4) admission costs. Summary of Background: VO is a serious disease with potentially devastating clinical consequences. At present, there is limited data on the epidemiology of VO in the United States as previous reports are based on older studies with small sample sizes. Methods: We used the Nationwide Inpatient Sample database and estimated that 228, 044 patients were admitted for VO in the United States between 1998 and 2013. Data were extracted on patient demographics, comorbidities, inpatient mortality, LOS, and inflation-adjusted hospitalization charges. Multivariable regression analyses were performed. Results: The incidence of VO admission was 4.8 per 100, 000, increasing from 8021 cases (2.9/ 100, 000) in 1998 to 16, 917 cases (5.4/100, 000) in 2013. Majority of patients were white (74%), male (51%), younger than 59 years of age (49.5%), and carried Medicare insurance (50%). The increase in incidence for male and females was similar. The mortality rate during hospital stay was 2.1%, decreasing from 2% in 1998 to 1.7% in 2006 and increasing to 2.2% in 2013. Risk factors for mortality included increased age, male sex, and higher comorbidity score. History of congestive heart failure [odds ratio (OR)=2.45], cerebrovascular disease (OR=1.92), liver disease (OR=2.33), hepatitis C (OR=2.36), and renal disease (OR=1.88) was associated with higher mortality rate. Mean LOS was 9.2 days, decreasing from 9.1 days in 1998 to 8.8 days in 2013. The mean estimated hospital charges for admission were $54, 599, however, this increased from $24, 102 in 1998 (total of $188.8 millions) to $80, 786 in 2013 (total of $1.3 billions). Conclusion: This condition is associated with lengthy and expensive hospital stays resulting in a significant burden to patients and the health care system.